DECLINE OF UNDERNOURISHMENT IN STUDENTS OF PUBLIC SCHOOLS ACCORDING TO CRITERION OF CDC (Fiep Bulletin - online, 2015)
The undernourishment is a world problem of public health. Estimations indicate that about 100 millions of children suffer moderate or high undernourishment around the world. In some regions of Brasil more than a half of the child population shows undernourishment, mainly in the North and Northeast. Eventhough, researches in Brasil indicate a decline on undernourishment index  in the Northeast from ten years ago to nowadays, from 28% to 18%. This research analizes the prevalence of normality and undernourishment in students from the public schools in metropolitan area of Fortaleza. The sample is constituted of 381 children from both sex, with age between 6 and 7 years old, selected by an aleatory way between the six regions of Fortaleza. The indexes of undernourishment, normality, overweight and obesity were done according to Centers of Disease Control and Prevention (CDC). The results showed 195 (51,2%) girls and 186 (48,8%) boys. According to Body Mass Index (BMI) was verified that; 4,6% of children are obese, 6,6% are overweight, 16,6% showed undernourishment and 72,2% are normal. Even analizing the results by regions and by sex, we verified that the normality was bigger than undernourishment, overweight and obesity. So we can conclude that Fortaleza shows a low index of undernourishment when compared to other cities of Northeast, according to bibliography. We suggest a causalistic research to identify the reasons of the undernourishment, then it can be avoided. But even with this decline, the undernourishment still constitutes a risk chart for children.
Keywords: Undernourishment; BMI; Public Schools.